Challenges and demand for modeling disorders of consciousness following traumatic brain injury. (March 2019) - O'Donnell, John C.; Browne, Kevin D.; Kilbaugh, Todd J.; Chen, H. Isaac; Whyte, John; Cullen, D. Kacy
Highlights: Traumatic Disorders of Consciousness (DoC) lack a preclinical model. The ubiquitous small animal models of TBI cannot produce prolonged unconsciousness. Unconsciousness is due to rotational acceleration—not impact—acting on brain mass. Rotational acceleration TBI in swine reliably produces prolonged unconsciousness. This model can provide controlled, data-rich, low-variability investigation of DoC. Abstract: Following severe traumatic brain injury (TBI), many patients experience coma — an unresponsive state lacking wakefulness or awareness. Coma rarely lasts more than two weeks, and emergence involves passing through a state of wakefulness without awareness of self or environment. Patients that linger in these Disorders of Consciousness (DoC) undergo clinical assessments of awareness for diagnosis into Unresponsive Wakefulness Syndrome (no awareness, also called vegetative state) or Minimally Conscious State (periodic increases in awareness). These diagnoses are notoriously inaccurate, offering little prognostic value. Recovery of awareness is unpredictable, returning within weeks, years, or never. This leaves patients' families with difficult decisions and little information on which to base them. Clinical studies have made significant advancements, but remain encumbered by high variability, limited data output, and a lack of necessary controls. Herein we discuss the clear and present need to establish a preclinical model of TBI-induced DoC, the significant challenges involved, and how such a model can be applied to support DoC research.